Drug-Coated Balloon-Oriented Angioplasty for Severe Symptomatic Atherosclerotic MCA Stenosis in Young Adults - Zhang, Yuyan; Chu, Xi; Meng, Yao; Zhang, Jun; Sun, Lili; Zhao, Wei; Zheng, Meimei; Yin, Hao; Wang, Wei; Zhang, Jinping; Song, Yun; Han, Ju (Frontiers in Neurology, 2022)
Purpose: The clinical significance of endovascular therapy in young patients with symptomatic intracranial atherosclerotic stenosis is not clear. We aimed to report our preliminary findings on the safety and effectiveness of a new endovascular treatment strategy, drug coated balloon (DCB)-oriented angioplasty for young adults with severe symptomatic atherosclerotic middle cerebral artery (MCA) stenosis. Methods: We retrospectively retrieved the data of seven young patients aged 21–32 years old with severe symptomatic atherosclerotic MCA stenosis treated with DCB-oriented angioplasty from January 2018 to October 2020. We collected clinical presentations, perioperative complications, and clinical and radiological outcomes. Results: The DCB was successfully dilated at the lesions in all seven patients and good antegrade perfusion was achieved in five. The other two patients underwent remedial stent implantation due to residual stenosis > 50% and unstable antegrade perfusion after DCB dilatation. However, none of the patients had perioperative complications. There were no recurrent ischemic symptoms after a mean clinical follow-up period of 15.4 ± 6.9 months. Repeat vascular images of the patients showed no restenosis at 3- or 6-month imaging follow-up periods. High resolution magnetic resonance imaging (HRMRI) was completed in all the patients before the angioplasty procedure and at follow-up. Focal eccentric wall thickening was present at the site of stenosis preoperatively; however, the plaques had disappeared by the time of follow-up for all patients. Conclusion: DCB-oriented angioplasty may be safe and effective for young patients with severe symptomatic atherosclerotic MCA stenosis.